2020
DOI: 10.3390/biomedicines8100434
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Astaxanthin Treatments Trigger the Hormesis of Human Astroglioma Cells by Up-Regulating the Cyclin-Dependent Kinase and Down-Regulated the Tumor Suppressor Protein P53

Abstract: Astaxanthin (AXT) is a xanthophyll carotenoid known to have potent anti-cancer effects via upregulation of the intracellular reactive oxygen species (ROS) levels, which triggers apoptosis of cancer cells. While several studies have shown that AXT has potential as an anti-cancer drug, its effects in glioblastoma multiforme cells remain relatively unknown. In this study, we investigated the effects of AXT in the astroglioma cell lines U251-MG, T98G, and CRT-MG. We found that the response to AXT varied between ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…These results show that unlike previously investigated cancer cell lines [21], the anticancer ability of AXT is restricted in GBM cell lines. This is consistent with our previous study showing that AXT has only a moderate apoptotic effect and shows beneficial effects in GBM cells [32].…”
Section: Axt Treatment Of Selected Gbm Cell Lines Do Not Trigger Cell...supporting
confidence: 94%
“…These results show that unlike previously investigated cancer cell lines [21], the anticancer ability of AXT is restricted in GBM cell lines. This is consistent with our previous study showing that AXT has only a moderate apoptotic effect and shows beneficial effects in GBM cells [32].…”
Section: Axt Treatment Of Selected Gbm Cell Lines Do Not Trigger Cell...supporting
confidence: 94%
“…Notably, HDFs exhibited a biphasic dose response to PRO (150 μM)/GEM treatments, indicating that, similarly to other natural compounds and also to some chemotherapeutics [ 32 , 33 , 34 , 35 ], PRO in combination with GEM may induce a hormetic effect. In addition, PRO/GEM treatments caused a hormetic response in MCF-7 cancer cells, suggesting a cautious use of natural compounds as anti-cancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Hormesis is a phenomenon of biphasic dose response in which a compound usually exhibits stimulatory or beneficial effects at low doses and inhibitory or toxic effects at high doses [ 32 , 33 , 34 , 35 ]. Hormetic effect should be considered in cancer therapy in order to optimize treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that it can inhibit lipid peroxidation and DNA damage, exerting neuroprotective effects. In addition, astaxanthin has been shown to affect the processes of tumor cell production, growth and apoptosis [16,17].…”
Section: Introductionmentioning
confidence: 99%